Измерение вертикальных смещений сооружений и анализ устойчивости реперов - Ганьшин В. Н. Владимир Николаевич; Стороженко А. Ф. Анна Федоровна; Буденков Н. А. Николай Алексеевич; Ильин А. Г. (Москва, Недра, 1981)
Авт. указаны на обороте тит. л.